2013
DOI: 10.1111/j.1574-6976.2012.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Host-selective toxins produced by the plant pathogenic fungusAlternaria alternata

Abstract: Host-selective toxins (HSTs) produced by fungal plant pathogens are generally low-molecular-weight secondary metabolites with a diverse range of structures that function as effectors controlling pathogenicity or virulence in certain plant-pathogen interactions. There are now seven known diseases caused by Alternaria alternata in which HSTs are responsible for fungal pathogenesis. The pathogens have been defined as pathotypes of A. alternata because of morphological similarity but pathological differences. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
298
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(303 citation statements)
references
References 175 publications
(439 reference statements)
2
298
0
3
Order By: Relevance
“…Al. alternata causes large economic losses of food and feed every year, because it not only produces melanin but a large variety of secondary metabolites such as carcinogenic alternariol (Pruß et al, 2014;Saha et al, 2012;Tsuge et al, 2013). As in other organisms, it was shown that melanin-deficient strains are more sensitive to UV light (Kawamura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Al. alternata causes large economic losses of food and feed every year, because it not only produces melanin but a large variety of secondary metabolites such as carcinogenic alternariol (Pruß et al, 2014;Saha et al, 2012;Tsuge et al, 2013). As in other organisms, it was shown that melanin-deficient strains are more sensitive to UV light (Kawamura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites from fungal pathogens are usually toxic to plants and are called phytotoxins which are divided into host-specific [83,84] and host non-specific toxins [85,86]. Some Alternaria-derived dibenzo-α-pyrones were approved as the host-specific phytotoxins including altenuene (1), alternariol (10), alternariol 9-methyl ether (11), alternuisol (15), and dehydroaltenusin (17) [9,10,37,39,41,45].…”
Section: Phytotoxicitymentioning
confidence: 99%
“…Significant levels of diversity in Alternaria species have also been reported using other molecular techniques such as microsatellites [34] and amplified fragment length polymorphism markers (AFLP) [35]. In addition to this, high levels of variation in Alternaria species have also been observed using other techniques like morphometric characters [36], structures of host-selective toxins (HSTs) [37] and protein analysis [38]. The isolates from the three sweetpotato cultivars (Excel, Beauregard and W-119) grouped together with some breeding lines in the subclusters of cluster I. Excel, Beauregard and W-119 originated from the USA and are used in the sweetpotato breeding programme at ARC-VOPI.…”
Section: Asian Journal Of Applied Sciences (Issn: 2321 -0893) Volumementioning
confidence: 93%